2015
DOI: 10.1097/qai.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Early Antiretroviral Therapy Is Protective Against Epilepsy in Children With Human Immunodeficiency Virus Infection in Botswana

Abstract: Background Seizures are common among patients with HIV/AIDS in the developing world and are associated with significant morbidity and mortality. Early treatment with combination antiretroviral therapy (cART) may reduce this risk by decreasing rates of central nervous system infections and HIV encephalopathy. Methods A case-control study of new onset epilepsy among children age 0-18 years with perinatally acquired HIV/AIDS followed in Gaborone, Botswana during the period 2003-2009 was conducted. Children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…Despite the limitations, this study provides needed and important data on the epidemiology and management of seizures in HIV-infected children. Our results which investigated seizures in HIV-infected children within the Southern African area can be compared to Bearden et al [28]'s previous work with a Botswanan cohort of HIV-infected children. In their study the authors were specifically interested in whether early ART treatment could prevent the onset of epilepsy in these children.…”
Section: Discussionsupporting
confidence: 58%
“…Despite the limitations, this study provides needed and important data on the epidemiology and management of seizures in HIV-infected children. Our results which investigated seizures in HIV-infected children within the Southern African area can be compared to Bearden et al [28]'s previous work with a Botswanan cohort of HIV-infected children. In their study the authors were specifically interested in whether early ART treatment could prevent the onset of epilepsy in these children.…”
Section: Discussionsupporting
confidence: 58%
“…Our study demographics are similar to what has been reported in prior studies of children in Gaborone. 29 However, compared with the overall population in Botswana, our study population was more urban, had higher levels of education, and had higher levels of literacy.…”
Section: Discussionmentioning
confidence: 59%
“…17,18 And as previously noted, certain infections such as HIV and malaria have known comorbidities with neurodevelopment, with recognition and early initiation of therapies potentially beneficial in these cases. 19 Furthermore, it is known that malnutrition plays a role in neurodevelopment, with nutritional disorders putting this population further at risk. 20,21 Thus, recognition of associated etiologies with common neurodevelopmental disorders in the developing world provides options for low-resource interventions with potential high impact.…”
Section: Methodsmentioning
confidence: 99%
“…23,41,48,59 Drug interactions between older ASDs and antimicrobials (such as antiretroviral drugs) are a major concern, as there are generally no enzyme-neutral drugs readily available in most LMICs. 19,60 An analysis of the availability, price, and affordability of ASDs conducted in 46 countries showed suboptimal availability and affordability of ASDs acted as a barrier to treatment. 27 In addition, pediatric formulations are largely unavailable in most developing countries, making dosing more challenging.…”
Section: Specific Diseases Epilepsymentioning
confidence: 99%
See 1 more Smart Citation